Unravelling discarded second-hand winter knitwear into reusable recycled material / Wan Nadhra Ixora Binti Wan Kamarulbaharin ... [et al.] - Wan Kamarulbaharin, Wan Nadhra Ixora; Saidan, Suriati; Saaidin, Husna; Zakaria, Muhammad Hisyam (Universiti Teknologi MARA, Perak, 2022)
Textile waste has become a worldwide problem. Malaysians dumped approximately 195,300 tonnes of fabric waste, causing Malaysian landfills with discarded textile to account for about 6.3% of the total 3.1 million tonnes of solid waste filling up landfills. The excessive amount of clothing in thrift shops is due to the fast fashion industry mass-producing clothing at rapid speed in a short time frame making the value of one garment plummet to dirt cheap with lower stitching quality. The objective of this study is to identify available discarded preloved winter knitwear as a suitable sustainable material and to propose an effective method for unrevealing knitwear into a reusable recycle material. The researcher applies qualitative research by preparing a semi-structured interview question and experimentation to gather the required data. The research resulted in a potentially reusable material able to use in producing new items. This study will help the consumers to reduce the number of textile waste in landfills by understanding the method of unveiling woven garments into a reusable recycle material for a potential new product.